Developing and validating the multidimensional industry commitment scales: The perspective of vocational high school students - Tuatul Mahfud; Nuraly Masum Aprily; Ida Nugroho Saputro; Ibnu Siswanto; Suyitno Suyitno (International Journal of Evaluation and Research in Education (IJERE), 2022)
Industry commitment plays a vital role in vocational education programs, especially in vocational high schools. The involvement of the industry is the key to the success of implementing vocational education. However, how to measure industry commitment in vocational learning is still not discussed. This study aimed to develop and test the validity of an industry commitment questionnaire. The industrial commitment questionnaire validation test gradually used three techniques, namely, content validity test, pilot test, and confirmatory factor analysis (CFA). The respondents were 390 culinary students of seven state vocational schools in Yogyakarta Special Region Province, Indonesia. This study revealed that industrial commitment can be measured by 12 items of industry commitment questionnaire consisting of four career opportunity items, two performance assessment items, four involvement/participation items, and two empowerment items. This study fills a gap in the assessment of industry commitment to engagement in vocational education programs. This study has implications for vocational education practitioners to evaluate the extent of industry commitment to vocational education programs.